Living donor liver transplantation can address disparities in transplant access for patients with primary sclerosing cholangitis - Fernanda Onofrio; Katina Zheng; Cherry Xu; Shiyi Chen; Wei Xu; Mary Vyas; Katie Bingham; Keyur Patel; Leslie Lilly; Mark Cattral; Nazia Selzner; Elmar Jaeckel; et al. (Hepatology Communications, 2023)
Background:. Liver transplantation (LT) is frequently lifesaving for people living with primary sclerosing cholangitis (PSC). However, patients are waitlisted for LT according to the model for end-stage liver disease-sodium (MELD-Na) score, which may not accurately reflect the burden of living with PSC. We sought to describe and analyze the clinical trajectory for patients with PSC referred for LT, in a mixed deceased donor/living donor transplant program. Methods:. This was a retrospective cohort study from November 2012 to December 2019, including all patients with PSC referred for assessment at the University Health Network Liver Transplant Clinic. Patients who required multiorgan transplant or retransplantation were excluded. Liver symptoms, hepatobiliary malignancy, MELD-Na progression, and death were abstracted from chart review. Competing risk analysis was used for timing of LT, transplant type, and death. Results:. Of 172 PSC patients assessed, 84% (n = 144) were listed of whom 74% were transplanted. Mean age was 47.6 years, and 66% were male. Overall mortality was 18.2% at 2 years. During the follow-up, 16% (n = 23) were removed from the waitlist for infection, clinical deterioration, liver-related mortality or new cancer; 3 had clinical improvement. At listing, 82% (n = 118) had a potential living donor (pLD). Patients with pLD had significantly lower waitlist and liver-related waitlist mortality (HR 0.20, p<0.001 and HR 0.17, p<0.001, respectively), and higher rates of transplantation (HR 1.83, p = 0.05). Exception points were granted to 13/172 (7.5%) patients. Conclusions:. In a high-volume North American LT center, most patients with PSC assessed for transplant were listed and subsequently transplanted. However, this was a consequence of patients engaging in living donor transplantation. Our findings support the concern from patients with PSC that MELD-Na allocation does not adequately address their needs.